Study of the athlete's posture and balance through photogrammetry and stabilometry when using mouthguards for sports (Research, Society and Development, 2021)
Mouthguards are intraoral devices that aim to prevent dental and maxillofacial trauma resulting from sports practice. As it is an interocclusal device, it is necessary to understand and know if it can interfere with the athlete's body balance, considering that the existence of the relationship between the temporomandibular system and postural control. The aim of this study was to evaluate the influence of individualized mouthguards on balance, head, jaw and shoulder posture of athletes and extract their account of the perception of use regarding possible changes in balance, body posture and sports performance. This study is a non-randomized clinical trial that included 65 athletes assisted by spontaneous demand at the Sports Dentistry Outpatient Clinic of the Dentistry School of the University of São Paulo (FOUSP). The use of individualized mouthguards had a significant influence on the variable glabellation distance (p=0.005). Regarding the report of the perception of use, 75.68% reported changes in balance and 70.28% in body posture, 70.28% reported improvement in performance and 67.56% improvement in sports gesture. It is concluded that the use of individualized mouthguards causes more confidence in athletes in the execution of exercises and, consequently, in sports performance.